Identification of a Prognostic Clinical Score for Patients With Recurrent or Metastatic Squamous Cell Carcinoma of the Head and Neck Treated With Systemic Therapy Including Cetuximab - Pogorzelski, Michael; Hilser, Thomas; Ting, Saskia C.; Kansy, Benjamin; Gauler, Thomas C.; Stuschke, Martin; Schmid, Kurt W.; Lang, Stephan; Grünwald, Viktor; Schuler, Martin; Kasper, Stefan (Frontiers in Oncology, 2021)
Cetuximab-based chemoimmunotherapy has been the standard of care for recurrent or metastatic squamous cell carcinoma of the head and neck (r/m SCCHN) for more than a decade. To date, no predictive or prognostic biomarkers have been established to further guide the systemic treatment with cetuximab-based chemoimmunotherapy in r/m SCCHN. Against this background, we retrospectively analyzed clinical and blood-based parameters from 218 r/m SCCHN patients treated with chemoimmunotherapy including cetuximab. Multivariate Cox-regression models were used to assess their prognostic or predictive value. Eastern Co-operative Oncology Group (ECOG) performance status (≥ 2), older age (≥ 61.8 years), anemia (hemoglobin < 11.80), and increased neutrophil-to-lymphocyte ratio (NLR ≥ 5.73) were independently and strongly associated with inferior overall survival (OS). To group patients according to risk profiles we established a prognostic clinical score (PCS) that can easily be used in clinical practice. The PCS stratified the cohort into low, intermediate, poor or very poor risk subgroups with median OS times of 23.4, 12.1, 7.5 and 4.0 months, respectively. Patients with low risk PCS had a prolonged progression-free survival (PFS) and increased overall response rate (ORR) under first-line cetuximab-based therapy. Interestingly, only patients with low and intermediate risk benefitted from the more intensive first-line cisplatin/cetuximab combination compared to carboplatin/cetuximab therapy, whereas the intensity of first-line treatment had no impact in the poor and very poor risk subgroups. Following external validation, particularly in the context of newly established first-line options, the PCS may guide clinical decision making and serve for stratification of patients with r/m SCCHN in future clinical trials.